Perancangan Sistem Informasi Pelaporan Barang Rusak Berbasis Website di Pengadilan Negeri Jambi Kelas 1A - Sepriano Sepriano; Dewi Rahayu; Dinda Syaqilla; Eka Saputra; Indo Masse (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Currently, the management of the damaged goods reporting at the Class 1A Jambi District Court still relies on manual procedures through verbal communication and physical logbooks. This mechanism is prone to recording errors, risks of document loss, and complicates real-time monitoring of repair statuses. This study aims to design a web-based Damaged Goods Reporting Information System to improve the effectiveness, transparency, and efficiency of internal asset management. The research method employs a qualitative approach with data collection techniques consisting of interviews, observations, and documentation. System development implements the Waterfall model, comprising requirement analysis, design, implementation, and testing phases. The result of the study deliver a web-based application that integrates features for report input, proof of damage photo uploads, admin validation, and real-time monitoring of repair status. This system successfully simplifies bureaucratic workflows, accelerates response times for damage handling, and minimizes administrative errors.